Age and Gender-specific Hepatitis C Continuum of Care and Predictors of Direct Acting Antiviral Treatment Among Persons Who Inject Drugs in Seattle, Washington - Corcorran, Maria A. (Drug Alcohol Depend, 2021)
BACKGROUND: Direct acting antivirals (DAAs) have revolutionized management of hepatitis C virus (HCV), but treatment uptake remains low among persons who inject drugs (PWID). We report the continuum of care for HCV and describe predictors of treatment with DAAs among PWID in Seattle. METHODS: We analyzed data from the 2018 Seattle area National HIV Behavioral Surveillance (NHBS) survey of PWID. Persons ≥18 years of age who injected drugs in the past year and completed the core NHBS survey, a local survey supplement, and rapid HCV antibody testing were included. Among those who screened HCV antibody positive, we calculated proportions and 95% confidence intervals for self-reported steps along the HCV care continuum. Multivariable logistic regression was used to calculate the adjusted odds (AOR) of having received DAA therapy. RESULTS: The sample included 533 PWID, 376 (71%) of whom tested positive for antibodies to HCV. Among those who were HCV antibody positive, 94% reported any prior HCV test, 81% reported a prior confirmatory test, and 68% reported a prior HCV diagnosis. Of those diagnosed, 26% had undergone treatment and 18% had been cured. In a multivariate model, being one year older (AOR 1.05 per year, 1.01-1.08) was predictive of DAA treatment, while homelessness (AOR 0.39, 0.19-0.80) and female gender (AOR 0.36, 0.16-0.78) were associated with a lower odds of DAA therapy. CONCLUSIONS: Despite widespread HCV testing among PWID in Seattle, treatment uptake remains low in the DAA era. In particular, treatment of women, younger adults and persons living homeless is lagging behind.